Graphene-based Biosensors for Dopamine Determination. (2017) - Fritea, Luminiţa; Tertiș, Mihaela; Le Goff, Alan; Cosnier, Serge; Săndulescu, Robert; Cristea, Cecilia
Abstract: Two different graphene/ β -cyclodextrin (CD)-based biosensors were elaborated for dopamine (DA) determination starting from glassy carbon electrode (GCE). First one was obtained by modifying GCE with reduced graphene oxide (RGO), CD and tyrosinase (Tyr) immobilized with a polyethylenimine film. The second biosensor was obtained after the incorporation of RGO functionalized with a new synthesized pyrrole- β -CD derivative and Tyr in an electropolimerized poly-amphiphilic pyrrole film. These two new approaches have resulted in selective and sensitive determination of DA in pharmaceuticals and real human samples.